Magic Efficacy of Pulsatilla to treat Polycystic Ovarian Syndrome - Islam, Md Mazharul; Chowdhury, Ashru Kana (Indian Journal of Integrative Medicine, 2023)
A complex condition known as polycystic ovarian syndrome (PCOS) affects 5–10% of women and is associated with hyperandrogenism, polycystic ovaries, persistent anovulation, insulin resistance, abdominal obesity, hypertension, and dyslipidemia. It is a typical cause of anovulatory infertility and is susceptible to change throughout a person’s lifetime due to changes in metabolism and fat. Although the cause of PCOS is uncertain, in-utero fetal programming may contribute to the condition’s emergence. Environmental and genetic factors cause metabolic and menstrual irregularities in PCOS. Polycystic ovarian insulin resistance syndrome, excessive body fat, and obesity-related illnesses like diabetes and cardiovascular disease are becoming increasingly common in Asian Indians. There is a need for complementary therapy that will reduce the symptoms of PCOS without causing side effects because of the negative consequences of conventional treatment, the high cost of care, post-surgical complications, and the patients who do not react to these interventions. Homeopathy is an alternative medical approach used well for various illness situations, including PCOS. A PCOS case is shown here to describe the beneficial effects of specialized homeopathic treatment. More researches are significant to confirm the efficacies of homeopathic medicines, low treatment cost, fewer side effects, and publicity of homeopathic success in curing PCOS are needed by the appropriate authorities.